O discurso humorístico nas charges da Tribuna do Norte - Luciano, Jociane da Silva (2013)
In this dissertation, we analyze the constitution and functioning of the humorous discourse in discursive genre cartoon from the recognition and analysis of the techniques of humor used to get the desired effects of meaning. We used the theoretical and methodological assumptions of French Discourse Analysis henceforth (AD) for the research. Specifically on the techniques of humor, we rely on authors like Possenti (1998) and Propp (1992) to see how these procedures are present in the cartoons and make the discourse of humor. To achieve this goal, ten (10) cartoons were analyzed dealing with episodes relating to the management of the mayor Micarla de Souza in the city of Natal, RN. These cartoons were published in the newspaper Tribuna do Norte during the year 2012. The research falls within the field of study of Applied Linguistics and is qualitative, interpretive nature. In the first part, we did a rescue of the foundations of discourse analysis, discussing the concept of interdiscourse, then we carry on about the notion of gender discourse from the perspective of AD, and the genre itself cartoon as we work with the cartoon as a discourse genre, and finally, we deal with this humor discourse in cartoons. We then developed some analyzes to illustrate the postulate that all text is founded upon certain conditions of enunciation; that the relationship between the cartoons and interdiscourse is a constitutive relationship that brings out certain cartoons/ discourses and not others, and especially what humor techniques are used strategically by the cartoonist, whose discursive decisions cause certain effects of meaning. The results of this paper find that discursive relations are relations of subjects and meanings, that the discourse of cartoon is built from other sayings and discourses, and that certain textual and discursive procedures/techniques, as parody, irony, lowering the other, the ambiguity and displacement are mobilized in the text to generate the possible effect of the comic, thus building the humor discourse of the cartoons analyzed